ASP.NET Core 5 for Beginners - Chilberto, Jeffrey (Packt Publishing, 2020)
Learn how to build web applications efficiently using ASP.NET Core 5 with the C# programming language and related frameworks Key Features Build web apps and services and cross-platform applications using .NET and C# Understand different web programming concepts with the help of real-world examples Explore the new features and APIs in ASP.NET Core 5, EF Core, Visual Studio, and Blazor Book Description ASP.NET Core 5 for Beginners is a comprehensive introduction for those who are new to the framework. This condensed guide takes a practical and engaging approach to cover everything that you need to know to start using ASP.NET Core for building cloud-ready, modern web applications. The book starts with a brief introduction to the ASP.NET Core framework and highlights the new features in its latest release, ASP.NET Core 5. It then covers the improvements in cross-platform support, the view engines that will help you to understand web development, and the new frontend technologies available with Blazor for building interactive web UIs. As you advance, you'll learn the fundamentals of the different frameworks and capabilities that ship with ASP.NET Core. You'll also get to grips with securing web apps with identity implementation, unit testing, and the latest in containers and cloud-native to deploy them to AWS and Microsoft Azure. Throughout the book, you'll find clear and concise code samples that illustrate each concept along with the strategies and techniques that will help to develop scalable and robust web apps. By the end of this book, you'll have learned how to leverage ASP.NET Core 5 to build and deploy dynamic websites and services in a variety of real-world scenarios. What you will learn Explore the new features and APIs introduced in ASP.NET Core 5 and Blazor Put basic ASP.NET Core 5 concepts into practice with the help of clear and simple samples Work with Entity Framework Core and its different workflows to implement your application's data access Discover the different web frameworks that ASP.NET Core 5 offers for building web apps Get to grips with the basics of building RESTful web APIs to work with real data Deploy your web apps in AWS, Azure, and Docker containers Work with SignalR to add real-time notifications to your app Who this book is for This book is for developers who want to learn how to develop web-based applications using the ASP.NET Core framework. Familiarity with the C# language and a basic understanding of HTML and C...